Potential and Constraints of Biopharmaceutical Plants in East Kalimantan Province - Junaidin Junaidin; Supriatno Salam; Erwin Samsul (Journal of Tropical Pharmacy and Chemistry, 2022)
Biopharmaceutical plants (drugs) in East Kalimantan Province have tremendous potential for the Farmers' Economy in particular and the Economy of Society in general. Farmers have not felt this potential because it faces existing obstacles. In this study, the Pharmaceutical Business Laboratory, Faculty of Pharmacy, Mulawarman University, will be analyzed for its role in finding solutions to existing obstacles. Research results are expected to be helpful in terms of the resource-advantage theory and in terms of Implications that can be done by Stakeholders, which aim that the potential of Biopharmaceutical Crops can bring the welfare of Farmers and Communities.